Nutrient Management Improvements in Forestry Species - Alvarado Hernández, Alfredo (2014)
Proper soil management and forest nutrition are key to maintaining the productivity of planted or natural forests. This article reviews related concepts and developments for Central American forests and focuses on relevant topics for forest managers including land evaluation, nutrient cycling, diagnosis of nutrient deficiencies, and limitations of general recommendations for liming and fertilizing.